Rate of convergence in the transfer theorem for min-scheme - Aksomaitis, Algimantas (Lietuvos matematikos rinkinys, 2008)
In this paper non-uniform estimate of convergence rate in the min-scheme is obtained. Presented results make the estimates, given in [1] and [2], more precise.